2017
DOI: 10.3892/ol.2017.5611
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid reverses cisplatin resistance in nasopharyngeal carcinoma cells by activating the mitochondrial apoptotic pathway

Abstract: Abstract. Despite improvements to radiotherapeutic strategies, resistance to adjuvant chemotherapy remains the main problem underlying the low 5-year survival rate in patients with nasopharyngeal carcinoma (NPC). In the present study, the human NPC cell line HNE1 was exposed to gradually increasing concentrations of cisplatin (CDDP) in order to establish a drug-resistant sub-cell line, HNE1/CDDP. HNE1/CDDP cells exhibited multidrug resistance and a prolonged doubling time, as compared with the parent HNE1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Radiotherapy and adjuvant chemotherapy have become the standard treatments for multiple types of cancer, including esophageal and nasopharyngeal carcinoma (1,2). Although radiotherapy is widely used to treat early-stage tumors, patients with advanced-stage tumors often experience failure of treatment mainly due to resistance to radiotherapy, resulting in recurrence and distant metastases (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy and adjuvant chemotherapy have become the standard treatments for multiple types of cancer, including esophageal and nasopharyngeal carcinoma (1,2). Although radiotherapy is widely used to treat early-stage tumors, patients with advanced-stage tumors often experience failure of treatment mainly due to resistance to radiotherapy, resulting in recurrence and distant metastases (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Li et al further revealed that ZA inhibited HNE‐1 cells proliferation and induced apoptosis through inducing S‐phase cell cycle arrest and activating mitochondrial apoptotic pathway, as protein levels of anti‐apoptotic Bcl‐2 gene were downregulated and genes of Bax, Bad, and Caspase‐9 were upregulated . Addition to the direct anti‐proliferative effect on HNE‐1 cells, ZA exhibited another effect of reversing cisplatin resistance in a drug‐resistant sub‐cell line, HNE1/CDDP, by arresting cell cycle at S‐phase and inducing mitochondrial apoptotic pathway, similar with the mechanism of its anti‐proliferation on HNE‐1 cells. In our present study, we demonstrated ZA induced apoptosis in the poorly differentiated nasopharyngeal carcinoma CNE‐2Z cells via triggering ROS generation and subsequently activating ClC‐3 chloride channel, indicating another mechanism by which ZA exerts the anti‐cancer effect in nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Zoledronic acid has shown its anti‐cancer effect in various types of carcinoma clinically . With regard to nasopharyngeal carcinoma, a subtype of head and neck cancers prevailing in Southeast Asia and Southeast China, ZA exerted its potential anti‐cancer effect in preclinical studies . Li et al demonstrated that ZA inhibited proliferation, migration and invasion of human nasopharyngeal carcinoma cell HNE‐1 via downregulating VEGF, MMP‐2, and MMP‐9 proteins expression .…”
Section: Discussionmentioning
confidence: 99%
“…Our current study further supports that down-regulation of MLH1 increases resistance to cisplatin in vitro and in vivo. Clinically, some NPC patients are resistant to cisplatin-based chemotherapy (50,51), a phenomenon that is probably linked to a deficiency in MLH1, compromising the cisplatin-induced apoptotic signaling (52).…”
Section: Discussionmentioning
confidence: 99%